Penerapan Manajemen Sumber Daya Manusia pada Agroindustri Tapai Singkong Skala Rumah Tangga - Amellia Rizky Febrianti; Bisma Ardika; Eka Dian Safitri; Wahyu Bintang Firmansyah; Tia Amalia Putri Yuristina (SUAN PUBLISHER, 2026)
Cassava tapai agroindustry is a traditional food-based enterprise that requires effective human resource management to support production activities and maintain product quality. This study aimed to analyze the implementation of human resource management in Tapai 32 Bondowoso Agroindustry. The research employed a descriptive qualitative method using a field study approach through observation, direct interviews with key informants, and documentation. The findings revealed that the recruitment system was conducted in a simple manner by prioritizing local community members without requiring specific technical skills. Job assignments were divided according to production stages, including cassava peeling, washing, steaming, yeast application, packaging, and product distribution. Employee training was carried out through direct practice and guidance from more experienced workers. The existing human resource management practices contributed to the smooth operation of the production process through clear task distribution and teamwork among workers. However, the management system remained informal and lacked structured documentation. Therefore, improvements in training programs and a more systematic human resource management approach are needed to enhance work effectiveness, productivity, and the long-term sustainability of the enterprise.